Design And Analysis Of Dual-Band Microstrip Antenna Using Dual Slot-Loading Technique At Wi-Fi Frequencies - Muhammad Irfan, Rosmi (2022)
The effect of dual slot-loading on rectangular microstrip antenna resonant frequencies has been investigated in this thesis. The dual-band microstrip antenna at wi-fi frequencies (2.4GHz and 5GHz) was designed using CST Studio Suite to obtain the result of the analysis. The microstrip antenna was constructed using the rectangular patch, and two frequency bands were obtained by adding a pair of parallel slots on the rectangular patch. The designed microstrip antenna is then fabricated and tested to measure its performance and compared to the simulation results from CST software.